Weed establishment in the second year after high pasture sowing rates - Armstrong, M.L.; Harrington, K.C.; Seefeldt, S.S. (New Zealand Plant Protection, 2002)
A field and an outdoor tray experiment were conducted to determine whether weed control benefits of high sowing rates of perennial ryegrass (Lolium perenne) continue into the second year after sowing Seeds of Scotch thistle (Cirsium vulgare) nodding thistle (Carduus nutans) and hedge mustard (Sisymbrium officinale) were sown into perennial ryegrass swards that were established 12 months earlier at differing densities Emerging weed seedlings were mapped at regular intervals to enable their fate to be followed Weed emergence and survival did not decline with increased ryegrass sowing rates indicating that 12 months after sowing the competitive ability of pasture sown at low density towards weeds equalled that of pasture sown at high density